Investigation on the Influence of Shear on Void Closure in Open‐Die Forging Processes. Issue 11 (2nd August 2022) - Gouverneur, Moritz; Bailly, David; Hirt, Gerhard
Abstract : In addition to achieving a specific target geometry and good material properties, one of the main goals of open‐die forging is to eliminate internal casting‐related voids, as they can lead to a critical failure of the component during application. Models designed to predict void closure often use simplifying assumptions to have limited validity for more complex stress and strain conditions. Therefore, the complex incremental forming during open‐die forging leads to inaccurate predictions of conventional models. In order to consider the complex stress conditions—mainly defined by shearing—and predict void closure more accurately, an extended model for the "Cicaporo" void closure model is created using a representative volume element simulation study. For validation, an ingot of AISI4140 with artificially introduced voids is forged, the voids are subsequently examined by X‐Ray, and their residual void volume is compared with the results of the extended and original void closure model. The results show that the void volume calculated by the extended model agrees well with the real void volume, and hence the new approach considering shear, can provide a much more accurate representation of the void closure in open‐die forging. Abstract : To guarantee the highest mechanical properties, internal defects such as voids must be eliminated during open‐die forging. However, models that predict void closure are generally only suitable for use in the core fiber. To overcome this limitation, an extended void closure model is presented to consider shear outside the core fiber.